Clinical Evaluation of Collagen-Induced Arthritis in Female Lewis Rats: A Comprehensive Analysis of Disease Progression and Severity - Mahnaz Babaahmadi; Nima Makvand Gholipour; Behnoosh Tayebi; Jed Pheneger; Ensiyeh Hajizadeh-Saffar; Mohamadreza Baghaban Eslaminejad; Seyedeh-Nafiseh Hassani (Cell Journal, 2023)
Objective: The collagen-induced arthritis (CIA) model is the most commonly studied autoimmune model of rheumatoidarthritis (RA). In this study, we investigated the usefulness of collagen type II emulsified in Freund's incompleteadjuvant (CII/IFA) as a suitable method for establishing RA in Lewis rats. The aim of the present study was to presenta straightforward and effective method for inducing CIA in rats.Materials and Methods: In this experimental study, animals were divided into two equal groups (n=5); control andCIA. Five rats were injected intradermally at the base of the tail with a 0.2 ml CII/IFA emulsion. On the seventh day,a 0.1 ml CII/IFA emulsion booster was injected. Arthritis symptoms that arose were evaluated at clinical, histological,radiological, and at protein expression levels to find out if the disease had been induced successfully.Results: Our finding showed a decreasing trend in the body weight during the RA induction period, while the arthritisscore and paw thickness were increased during this period. The results of the enzyme-linked immunosorbent assay(ELISA) for serum samples revealed that the levels of proinflammatory cytokines, interleukin (IL)-1β, IL-6, IL-17, andtumor necrosis factor (TNF)-α and anti-CII IgG were significantly increased in CIA rats compared to the control group.After CIA induction, the level of anti-inflammatory protein IL-10 was decreased significantly. Radiographic examinationof the hind paws showed soft tissue swelling, bone erosion, and osteophyte formation in CIA rats. Additionally, basedon histological evaluations, the hind paws of the CIA group showed pannus formation, synovial hyperplasia, and boneand cartilage destruction.Conclusion: It seems that CII/IFA treatment can be an appropriate and effective method to induce RA disease in Lewisrats. This well-established and well-characterized CIA model in female Lewis rats could be considered to study aspectsof RA and develop novel anti-arthritic agents.